Public libraries in crisis times - Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2010)
We analyze how the present economic crisis is influencing public libraries, and what initiatives must be taken to help users who are unemployed and who face economic difficulties. We also study the increase in library users, the budget reductions, the need to give priority to educational and social activities to help the users who are most in need, and the possibilities of cooperation with public institutions devoted to promoting employment and lifelong learning opportunities. Finally, we explain the case of the regional library in Murcia (Biblioteca Regional de Murcia), which has designed and implemented a program called "Library, job center".